Preoperative neutrophil‐to‐lymphocyte ratio predicts malignancy and recurrence‐free survival of solid pseudopapillary tumor of the pancreas. Issue 2 (30th April 2019) - Yang, Feng; Bao, Yun; Zhou, Zhongwen; Jin, Chen; Fu, Deliang
Abstract: Background: Systemic inflammatory markers such as neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) have been shown to be prognostic for many types of pancreatic malignancy. The aim of this study was to evaluate the prognostic role of these markers in patients with solid pseudopapillary tumor of the pancreas (SPTP). Methods: Patients who underwent surgical resection for histologically confirmed SPTP were retrospectively reviewed in our institution. Preoperative NLR and PLR were calculated. Clinicopathologic data were correlated with the presence of malignant potential and recurrence‐free survival (RFS). Results: A total of 113 patients with SPTP were included in this study. Of them, 23 were men and 90 were women, with a median age of 35 years (interquartile range, 25‐44). The optimal cut‐off values for malignant SPTP were 3.22 for NLR, and 75.5 for PLR, respectively. Univariate analysis showed that high NLR (>3.22) and white blood cell count more than 9.96 × 10 9 /L were predictive of a malignant SPTP. Meanwhile, high NLR ( P  = 0.001) and age more than 35 years ( P  = 0.026) were associated with worse RFS. On multivariable analyses, high NLR was the only independent predictor of malignant SPTP (odd ratio 6.871; 95% confidence interval [CI], 1.482‐31.864; P  = 0.014) and RFS (hazard ratio 12.633; 95% CI, 1.758‐90.790; P  = 0.012). Conclusions: This study highlights the supportive role of preoperative NLR in predicting malignancy and RFS of SPTP patients. Further studies including a larger cohort of patients are needed to corroborate our findings.